Correlating climate with late-winter wetland habitat in the Rainwater Basin, south-central Nebraska - Robichaux, Rex Michael (Kansas State University, 2010)
The Rainwater Basin Wetland Complex of south-central Nebraska is a region of great climatic variability, as well as tremendous ecological importance. The Rainwater Basin Wetland Complex is located at the focal point of the Central North American migratory bird flyway, and supports in excess of twelve million birds during the spring migration period. The physical landscape has been significantly altered from its pre-settlement state by agricultural conversion via the draining of over ninety percent of the native wetlands. Due to the region’s highly variable continental climate, interannual wetland water levels are also highly variable and currently unpredictable. I have used multi-year analysis, including the construction of a regional water budget assessment, to study which climatic variables play the most crucial role in the late-winter filling of wetlands. Research objectives were met by analyzing ten cold season (Oct – Feb) climatic variables and an annual measure of wetland area for five years, in order to better understand possible climatic drivers of wetland hydrologic functioning levels in March. Longer time series of winter season climatic information were also assessed to help place the recent and more detailed analysis into a longer climatic context. Research results will aid local management agencies in the future through enhanced knowledge of how climatic variation impacts wetland function. Seasonal precipitation and temperature was favored by the linear regression analysis, while the multiple regression analysis placed higher emphasis on February evapotranspiration rates, February snow depth, and February snowfall. Lastly, the hydrologic water budget that was created for the study area had several highly correlated output variables with basin-wide flooded hectares, particularly annual snow storage.
Keywords: Climate; Wetlands; Human-environment; Water budget; Applied Climatology; Nebraska; Geography (0366)